Rain fade characteristics analyses for V-band link in tropical region - Badron, Khairayu; Ismail, Ahmad Fadzil; Islam, Md. Rafiqul; Abdullah, Khaizuran; Din, Jafri; Abd Rahman, Tharek (2010)
A decade ago, the operating frequencies of most available satellites in the tropics were C band, S-band and Ku-band. The V-band satellite links were initially confined mainly to temperate regions. Recently however, this new service has gradually been introduced worldwide including the tropical regions. In the future, new satellites in the tropical and equatorial will also have no alternative but to operate at V-band and higher frequencies due to spectrum limitations. Therefore, it is very critical to be able to predict accurately the likely impairment to be encountered on a given link in order to plan the services economically. The predicted value of signal loss and fading are used to determine the design parameters. This paper aimed to discuss the seasonal, diurnal and possible fade mitigation technique that can be used and the challenges to be able to use V-band frequency in tropical region in the future.